Unusual presentation; seeding of tumor after biopsy for hepatocellular carcinoma - Aksoy, Asude; Karabulut, Koray; Artas, Hakan; Kilicarslan, Ahmet; Usta, Sertac; Bahcecioglu, Ibrahim Halil (Professional Medical Publications, 2016)
Hepatocellular cancer is one of the most common and fatal cancer tumor worldwide. However, the obtained results are questionable in terms of medical treatment of hepatocellular cancer. The muscle, soft tissue and cutaneous metastases of hepatocellular cancer, for instance, are rare and may result from interventional procedures. Seeding of tumor along the biopsy needle upon percutaneous biopsy is a very rare phenomenon. We report a very rare case of a 79 -year-old man, known to be hepatitis C virus carrier with a metastatic tumor in abdominal wall caused by seeding of tumor after three years following a percutaneous biopsy procedure. Even years later, after a biopsy procedure for diagnostic purposes and may be soft tissue metastases. This complication is a very rare condition that should not be ignored but can be observed. The biopsy requirement should be questioned closely and avoided unnecessary biopsy procedures.
Keywords: Biopsy; Hepatocellular carcinoma; Seeding